Statement of Removal (International Journal of Sustainable Engineering, 2020)
Article title: Biodiesels powered in-cylinder common rail direct injection (CRDi) Assisted Homogeneous Charge Compression Ignition (HCCI) engine Authors: S.B. Nagesh, N.R. Banapurmath, T.K. Chandrashekhar, S.V. Khandal Journal: International Journal of Sustainable Engineering Version of Record Published Online: 08 July 2020 DOI: https://doi.org/10.1080/19397038.2020.1780335 Due to a publisher error, source files associated with a different published article (Reza Khalifeh & Hossein Esmaeili, 2020, Biodiesel production from goat fat using calcium oxide nanocatalyst and its combination with diesel fuel to improve fuel properties, International Journal of Sustainable Engineering, DOI: 10.1080/19397038.2020.1780336), were incorrectly used during the production stages of the above article. We have removed this incorrect version of Nagesh et al. and published the correct version under a new DOI using the correct source files. The correct version of the article can be found here: https://doi.org/10.1080/19397038.2020.1811012 We apologise to the authors for this error.